2020
DOI: 10.1101/2020.02.27.20028829
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission potential of COVID-19 in South Korea

Abstract: Since the first identified individual of 2019 novel coronavirus (COVID-19) infection on Jan 20, 2020in South Korea, the number of confirmed cases rapidly increased. As of Feb 26, 2020, 1,261 cases of COVID-19 including 12 deaths were confirmed in South Korea. Using the incidence data of COVID-19, we estimate the reproduction number at 1.5 (95% CI: 1.4-1.6), which indicates sustained transmission and support the implementation of social distancing measures to rapidly control the outbreak.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 25 publications
3
18
0
2
Order By: Relevance
“…1.6, 1.9) which is in accordance with the estimates of the reproduction numbers retrieved from studies conducted in China, Brazil, Korea, Peru, South Africa and Iran that lie in the range of 1.5-7.1 [31][32][33][34][35][36][37][38][39][40]. In contrast, even lower estimates of ( <1) that have been reported in Singapore and Australia can be correlated with the implementation of early strict social distancing interventions in these countries [41,42].…”
Section: Discussionsupporting
confidence: 86%
“…1.6, 1.9) which is in accordance with the estimates of the reproduction numbers retrieved from studies conducted in China, Brazil, Korea, Peru, South Africa and Iran that lie in the range of 1.5-7.1 [31][32][33][34][35][36][37][38][39][40]. In contrast, even lower estimates of ( <1) that have been reported in Singapore and Australia can be correlated with the implementation of early strict social distancing interventions in these countries [41,42].…”
Section: Discussionsupporting
confidence: 86%
“…For instance, very few deaths have been reported so far in South Korea [33]. In this country, there is a large excess of young women in a cluster of SARS-CoV-2 infections associated with the Shincheonji Church of Jesus [34]. The higher number of young people among cases, widespread testing and better management of the epidemic might explain the fewer numbers of reported fatalities.…”
Section: Interpretation and Implicationsmentioning
confidence: 99%
“…appeared, and all of the places where the case patients had gone (eg, hotels, markets, and health facilities) were disinfected. 3 On February 21, when epidemiologic studies revealed 2 main sources of transmission, those places were defined as "special care zones" where a specialized team focused on controlling transmission, 9 and the alert level was elevated to the highest (severe). 10 Rapid diagnosis and widespread testing were other areas of focus in Korea.…”
mentioning
confidence: 99%